2017
DOI: 10.1038/s41598-017-16474-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum vascular endothelial growth factor is associated with acute viral encephalitis in Bangladeshi children

Abstract: Encephalitis causes significant global morbidity and mortality. A large number of viruses cause encephalitis, and their geographic and temporal distributions vary. In many encephalitis cases, the virus cannot be detected, even after extensive testing. This is one challenge in management of the encephalitis patient. Since cytokines are pivotal in any form of inflammation and vary according to the nature of the inflammation, we hypothesized cytokine levels would allow us to discriminate between encephalitis caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…Nevertheless, the strong positive correlation between VEGF and IL-1RA serum levels was observed exclusively in non-neurological disease, suggesting a distinct mechanism of inflammation control in the neurological disorder. Elevated levels of serum VEGF were observed in children with viral encephalitis (51), in untreated patients with HIV-associated encephalopathy (52), and in patients with severe dengue (53,54). On the hand, EGF levels were increased in CSF of patients with neurological manifestations and did not show significant correlations with other molecules.…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, the strong positive correlation between VEGF and IL-1RA serum levels was observed exclusively in non-neurological disease, suggesting a distinct mechanism of inflammation control in the neurological disorder. Elevated levels of serum VEGF were observed in children with viral encephalitis (51), in untreated patients with HIV-associated encephalopathy (52), and in patients with severe dengue (53,54). On the hand, EGF levels were increased in CSF of patients with neurological manifestations and did not show significant correlations with other molecules.…”
Section: Discussionmentioning
confidence: 94%
“…In the process of full-text revision, 88 articles did not meet the eligibility criteria and were excluded for different reasons, as outlined in Fig 1 based on PRISMA guidelines (_((((xxx))))_)[ 39 103 ]. In some of the excluded articles, the study was conducted to compare cytokines levels in other illnesses or different stages of encephalitis, all lacking control groups (_((((xxx))))_)[ 44 , 45 , 47 , 50 , 53 , 54 , 64 66 , 69 , 71 , 72 , 74 76 , 80 86 , 89 , 90 , 94 , 95 , 100 103 ]. There were articles whose results could not be included in this review because of being in vivo, in vitro, case reports, review articles, and conference abstracts (_((((xxx))))_)[ 39 , 40 , 42 , 46 , 49 , 51 , 52 , 55 , 57 , 59 , 61 , 63 , 67 , 68 , 73 , 78 , 79 , 93 , 97 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…Xing et al (2020) used nextgeneration metagenomic sequencing to diagnose viral encephalitis, achieving an AUC of 0.659 (95% CI: 0.566-0.751). Mori et al (2017) found serum vascular endothelial growth factor was able to discriminate virus-positive and virus-negative encephalitis in a study of Bangladeshi children with an AUC of 0.82 (95% CI: 0.66-0.98). The primary infection and replication of the major causative agents of VEVM usually occur in the oral cavity (Thompson et al, 2012;Rozenberg, 2013).…”
Section: Discussionmentioning
confidence: 96%